Penggunaan Pembenah Tanah untuk Pertanian Padi Organik di Kabupaten Blora: Penelitian - Waskitoaji, Wihatmoko; Yasir, Muh; Iksan, Zainuri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Blora Regency is one of the national rice production centers in Central Java Province. The history of rice farming in this region has been well established since the era of the Mataram Kingdom and continued through the period of Indonesian independence. During the New Order government, the use of chemical fertilizers was heavily promoted to increase agricultural productivity. However, it has recently been recognized that the continuous and long-term use of chemical fertilizers has led to soil fertility degradation and a decline in productivity. Over time, maintaining productivity has required increasing amounts of chemical fertilizers each year. Aware of this vicious cycle, farmer groups in Blora Regency have started to move away from chemical fertilizers and transition toward organic farming practices. To support soil restoration efforts and improve the productivity of organic rice fields, the National Research and Innovation Agency introduced a microbe-based soil ameliorant. As a result, the health of rice fields improved, as evidenced by rice yields reaching 9 tons per hectare without the use of chemical fertilizers. Through organic farming practices supported by microbe-based soil ameliorants, production costs were significantly reduced, while organic rice could be sold at a higher price. This has the potential to enhance the welfare of farmers in the region.